Adaptando-se à cultura brasileira : correlatos do bem-estar de estudantes estrangeiros de pós-graduação - Bello, Kissel Quintana (2015)
Considering the mobility of students around the world, in which those students coming from the Latin America represent a significant percentage, it is important to know what the factors that affect the subjective well-being of students in the adaptation process are. The experiences that involve the students from Latin America in their acculturation process, whether of more or minor impact, are related to their affect, to changes that happen in the social and family organization, how to dress, different types of food, musical preferences and how to behave. These experiences are significant for students, either positively or negatively in the integration process. Based on the literature on well-being and acculturation, this work aims at investigating the relations between subjective well-being, acculturation strategies, coping strategies and human values in foreign postgraduate from Latin America whose native language is Spanish and who go through an adaptive process in Brazil. For this, two studies were conducted. In Study I, participants were 103 sojourners who are currently enrolled at a postgraduate program in any Brazilian university. From this total, 54 were men and 49, women from 13 countries in Latin America, who answered the following online instruments in Spanish: sociodemographic information, Acculturation Index Scale, Coping Strategies Inventory, Life Satisfaction Scale, Job-Related Affective WellBeing Scale and the Basic Values Questionnaire. Results indicate the main use of two acculturative strategies: integration (35%), considered as the one that provides better adaptive results and greater well-being, and marginalization (35%), considered as the one that decreases the well-being. Regarding coping strategies, the use of two main strategies have been identified: problem solving and social support, which allow the student an appropriate adjustment in the host country with a decrease in stress. With respect to evaluative priorities of students, those considered most important were the values of existence, supra-personals and interactive. Men and women differ whit respect to coping strategies and acculturation, with women having higher averages in social support strategies, wishful thinking and emotional expression, and with the level of identification with the host country. The variables that predict SWB in a positive way are cognitive restructuring, normative values, experimental values and acculturation with Brazil. Those which do negatively are wishful thinking and existence values. For Study II, 14 interviews were conducted with Latin American students currently registered in a postgraduate program at the Universidade Federal de Espirito Santo. They are 07 men and 07 women, with ages ranging from 25 to 35, who are in Brazil for a xi minimum of 6 months. For this group, the main acculturative strategies used were integration and separation. With regard to coping strategies, social support has been identified with greater emphasis. In respect regard to life experiences, these were related to the language, search for accommodation (housing), the process for documents, living costs, and health services. Despite several limitations of this work, it brings contributions to multicultural research in Brazil and the construction of knowledge that can assist in proposing actions and programs promoting adequate adaptation to the encouragement of foreign student’s well-being in search of its development in Brazil.